(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Nobody might at any point imagine that this world would come at a halt in 2020, when the Covid 19 previously hit nobody accepted it could get such gigantic changes which would change the world as far as we might be concerned. It welcomed on many changes like work-from-home, social separating, changes in how cleanliness is kept up with and with it hits to various enterprises as well as an opportunity to arrive at new levels regarding innovation, particularly in lodgings. With the requirement for contactless assistance during the pandemic, the upsides of an AI attendant turned out to be significantly additionally articulated. The study descriptive in nature and adopted snowball sampling for collecting the data. The study the impact of covid -19 on the usage of artificial Intelligence, regression analysis was applied and found that among AI and RS AI (Chat-bots, Motion Detectors, Voice Recognition System) and RS (Online Reservation AI TOOLS INFLUENCING GUEST IN HOTELS 69 Portal), RS is relatively more important than the AI in explaining the guest intensity to stay. Study also explained that customer age is not significantly (0.103) impacted the guest intensity to stay in hotel.